Exploring & bridging the gap in pharmaceutical care needs of diabetic patients: an action research approach / Daphne Gima - Gima, Daphne (2017)
Type 2 diabetes mellitus remains a major health problem with a 20.8% prevalence in Malaysia. 80.6% of patients diagnosed with diabetes receive treatment in public health facilities which necessitated the expansion of roles of healthcare providers such as pharmacists into specialized diabetes care. Diabetes Medication Therapy Adherence Clinic (DMTAC) is a service run by pharmacists for diabetes medication therapy management and is available in most government health facilities. This was a qualitative study which used the action research approach to identify gaps and feasible improvements in the DMTAC service of Hospital Putrajaya, which is an endocrine centre. Data was collected from semi-structured interviews and field observations. This study found that the DMTAC service is appreciated by patients particularly due to the good rapport with pharmacists and is beneficial as a platform for diabetes education and discussion. However, the DMTAC service also has issues of unoptimized work flow as well as lack of visibility and utility. As a diabetes care model in general, the hospital lacks interprofessional collaboration among different diabetes care providers. Patients were also found to have issues with lack of self-care, which can be improved by better patient-provider communication to enhance behaviour modification. While some improvements can be made by the DMTAC pharmacists team alone, such as institution of a full time DMTAC pharmacist, some of the more critical barriers relate to the health care system and requires multidisciplinary collaboration towards a better diabetes care model.